Effects of Coconut Milk Powder on The Characteristics of Tongka Langit Banana Ice cream - Helen C D Tuhumury; Erynola Moniharapon; Yulinati Porudara (Tropical Small Island Agriculture Management, 2022)
The objective of this study was to determine the effects of coconut milk powder on the characteristics of Tongka Langit Banana ice cream. A completely randomized experimental design was applied in this research with coconut milk powder concentrations based on the weight of full cream milk used as a control. Hence, the levels of treatment were as follows: control (full cream milk), 25%, 50%, 75%, and 100% coconut milk powder. The results showed that Using coconut milk as a milk substitute in the preparation of Tongka Langit banana ice cream has affected its physicochemical and sensory properties but has no effect on vitamin C. With a fat content of 4.93%, a protein content of 0.77%, vitamin C content of 0.67%, total solids of 30.10%, and a melting time of 54'33', coconut milk at 100% by weight of milk was the appropriate concentration for producing ice cream with the best physicochemical and sensory properties.